Terminal problem? The case for a market-based airport slot allocation system - Kristian Niemietz (Institute of Economic Affairs (IEA), 2022)
Since the mid-1980s, the UK's aviation sector has undergone substantial liberalisation. This was a great success story as far as it went. But two major components have bucked that overall liberalisation trend: airport capacity, and the allocation of take-off and landing slots. These are the two remaining islands of central planning in an otherwise liberalised sector.At congested airports, airport operators have little control over the allocation of take-off and landing slots. If an airline has used a particular slot in the past, it has an automatic right (subject to some conditions) to carry on using it - indefinitely. The remainder of the slots are allocated by a quango, via an administrative process, under retained EU law (ultimately derived from the International Air Transport Association (IATA)).As a result of the 'grandfathering' of slots, most slots at large airports are simply held by the airline that has always held them. This distorts the market in favour of well-established incumbents. It is the main reason why large European airports continue to be dominated by nationallegacy carriers. Despite certain exceptions to the slot allocation rules, the market remains distorted. There is scope for major improvements.As in many other areas, Brexit is a double-edged sword when it comes to aviation. Brexit enables the UK to replace the EU/IATA slot allocation rules with an alternative system. This could mean replacing it with a more liberal and market-based alternative - but it could also mean replacing it with an even more dirigiste one, under which slots are allocated on the basis of political considerations.A more liberal alternative would mean introducing a primary market for airport slots. That could be done by a simple auction, or by congestion pricing, or it might be possible to allow airport operators to devise whatever slot pricing mechanism they see fit, and rent out airport slots to whoever they choose. Grandfathered rights would be phased out, and the slot allocation rules would cease to apply.Taken to the fullest extent, this could mean different things in practice. Some airports might use periodic slot auctions, under which slots go to the highest bidder. Auction design and auction rules could then differ from airport to airport. Other airports might use a system of dynamic runway pricing, in which they set market-clearing prices for slots. It could also lead to the emergence an altogether different allocation mechanism.
Keywords: 330